EVALUASI PROGRAM PEMBANGUNAN SISTEM DRAINASE JALAN BERSKALA LINGKUNGAN DALAM MENGATASI BANJIR DI KOTA PEKANBARU TAHUN 2020 - Ardiansyah "; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Drainage is the natural or artificial removal of water masses from the surface or subsurface of a place. In the author's research, the construction of a drainage system is the responsibility of the Department of Public Housing and Residential Areas of Pekanbaru City. The problem raised in this study is that during the current rainy season, floods often occur, this is because the drainage system has not functioned optimally, and many in the neighborhood around Pekanbaru do not have drainage. This study aims to determine the analysis of the Environmental Scale Road Drainage System Development Program Evaluation in 2020 in Pekanbaru City. Data collection techniques were carried out by interviews, and documentation. While the data analysis technique is done with qualitative data analysis. In conducting this research, the researcher used a qualitative research type. The type of research is descriptive, which is a report of people containing data quotes to provide an overview of the presentation of the report, the location of the research is carried out in the city of Pekanbaru, especially in the Department of Public Housing and Residential Areas of Pekanbaru City and also in the location of the program. by the Department. The techniques used to collect data in this researcher are (1) interviews, (2) observations, and (3) documentation. The results of this study indicate that the Environmental Scale Road Drainage System Development Program Evaluation in 2020 has not been carried out optimally. The inhibiting factors in carrying out the road drainage system development program are limited human resources, limited budget, lack of public awareness. Keyword: Evaluation, Program, Development, Drainage Syste